STEAP4 inhibits cisplatin-induced chemotherapy resistance through suppressing PI3K/AKT in hepatocellular carcinoma - Binhui Xie; Baiyin Zhong; Zhenxian Zhao; Jie Hu; Jianqiong Yang; Yuankang Xie; Jianhong Zhang; Jianting Long; Xuewei Yang; Heping Li (Cancer & Metabolism)
Abstract Chemotherapy resistance is the leading cause for hepatocellular carcinoma (HCC)-induced death. Exploring resistance generation mechanism is an urgent need for HCC therapy. Here, we found STEAP4 was significantly downregulated in HCC patients with recurrence. Patients with low STEAP4 had poor outcome, suggesting STEAP4 might inhibit chemotherapy resistance. Cell viability assay, colony formation assay, apoptosis assay, soft agar growth assay, and tumor animal model showed STEAP4 inhibited cisplatin resistance. Mechanism analysis showed STEAP4 inhibited PI3K/AKT pathway through directly interacting with AKT. Double knockdown of STEP4 and AKT significantly inhibited cisplatin resistance. We also found STEAP4 expression was negatively correlated with PI3K/AKT pathway activity in clinic specimens. In summary, our findings suggested STEAP4 inhibited cisplatin resistance through suppressing PI3K/AKT pathway activity, providing a target for HCC therapy. Graphical Abstract